Excitation of a higher order transverse mode in an optically pumped In0.15Ga0.85N/In0.05Ga0.95N multiquantum well laser structure - Hofstetter, Daniel; Bour, David P.; Thornton, Robert L.; Johnson, N. M. (My University, 1997)
We report a comparison between measured and calculated far field data for an optically pumped In0.15Ga0.85N/In0.05Ga0.95N multiquantum well laser structure with AlGaN cladding layers. Optical pumping of the semiconductor device was performed with a pulsed 337 nm N2 laser, whose beam was focused to a narrow stripe. A thin upper cladding layer allowed efficient pumping of the In0.15Ga0.85N/In0.05Ga0.95N laser structure. Despite high distributed cavity losses of at least 30 cm – 1, and although gain occurred in the small active region only, the seventh order transverse mode was supported in a waveguide formed by the entire 5-µm-thick epitaxial layer structure. Excellent agreement is demonstrated between measured and calculated far field patterns of the lasing mode.